Identification and characterization of the BRI2 interactome in the brain - Filipa Martins (Nature Portfolio, 2018)
Abstract BRI family proteins are ubiquitous type II transmembrane proteins but BRI2 is highly expressed in some neuronal tissues. Possible BRI2 functions include neuronal maturation and differentiation. Protein complexes appear to be important in mediating its functions. Previously described BRI2 interactors include the Alzheimer’s amyloid precursor protein and protein phosphatase 1, but clearly the identification of novel interactors provides an important tool to understand the role and function of BRI2. To this end three rat brain regions (cerebellum, hippocampus, and cerebral cortex) were processed by BRI2 immunoprecipitation; co-precipitating proteins were identified by Nano-HPLC-MS/MS. The pool of the brain regions resulted in 511 BRI2 interacting proteins (BRI2 brain interactome) of which 120 were brain specific and 49 involved in neuronal differentiation. Brain region-specific analyses were also carried out for cerebellum, hippocampus, and cerebral cortex. Several novel BRI2 interactors were identified among them DLG4/PSD-95, which is singularly important as it places BRI2 in the postsynaptic compartment. This interaction was validated as well as the interaction with GAP-43 and synaptophysin. In essence, the resulting BRI2 brain interactome, associates this protein with neurite outgrowth and neuronal differentiation, as well as synaptic signalling and plasticity. It follows that further studies should address BRI2 particularly given its relevance to neuropathological conditions.